Methods and Design Principles for Financial Innovation, Explaining the Supply Side for Interoperability in Finance- and Insurance-Tech The INFINITECH Applications and Solutions Part II - Serrano, Martín (NowOpen, 2023)
In this second part of the INFINITECH book series, which is a series of three books, the basic concepts for Fintech referring to the diversity in the use of technology to underpin the delivery of financial services are reviewed. The demand and the supply side in the financial sector are demonstrated, and further discussed is why Fintech is the focus of industry nowadays and the meaning for waves of digitization. Financial technology (FinTech) and insurance technology (InsuranceTech) are rapidly transforming the financial and insurance services industry. An overview of Reference Architecture (RA) for BigData, IoT and AI applications in the financial and insurance sectors (INFINITECH-RA) is also provided. Moreover, the book reviews the concept of innovation and its application in INFINITECH, and innovative technologies provided by the project for financial sector practical examples.